Investigating SiC MOSFET body diode's light emission as temperature-sensitive electrical parameter. (September 2018) - Ceccarelli, L.; Luo, H.; Iannuzzo, F.
Abstract: In this paper, the light emission of SiC MOSFETs during reverse conduction, caused by the Light Emission Diode (LED)-like behaviour of the body diode, is studied and investigated. The photoemission from a 1.2 kV/20 A commercial device has been measured experimentally using a silicon photodiode. A behavioural characterization of the light output under different junction temperatures and current values has been performed. This allows the implementation of a fast, inexpensive and non-invasive temperature sensing strategy for high-voltage SiC MOSFET chips based on the measurement of light emission during reverse conduction. Highlights: The photoemission from a 1.2 kV/20 A commercial SiC power MOSFET has been measured experimentally using a silicon photodiode; A behavioural characterization of the light emission under different junction temperatures and current values has been carried out on two SiC MOSFET samples; The photodiode output voltage could be correlated to the light emission intensity, changing current and case temperature, and was proven to be a promising temperature-sensitive electrical parameter; A first proof of concept of the implementation of a fast, inexpensive and non-invasive temperature sensing strategy for high-voltage SiC MOSFET chips based on light emission is provided.